The Role of The Government in Countering Mayantara Crime in Indonesia - Saidul Fikri; Muhammad Hatta; Furqan Pratama; Hafiz Fiqi Delmizar; Faisal Reza; Salamuddin Salamuddin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Along with the rapid and advanced development of the times, human thinking is also increasingly developing, including in terms of technology. Technological advances have brought great changes in human life. The rapid development of technology in Indonesia is accompanied by an increase in cybercrime, which poses a serious threat to national security and the country's economy. The types of crimes include various illegal acts such as data theft, online fraud, hacking, and the spread of malware. This research aims to analyze the role of the government in tackling violent crime in Indonesia, by highlighting regulatory aspects, strengthening infrastructure, and cooperation with various parties. The results of the study show that the Indonesian government has made efforts to tackle cybercrime by implementing regulations such as the Electronic Information and Transaction Law (ITE Law) and strengthening cybersecurity infrastructure. Cooperation with various parties and the community has also been carried out to increase digital literacy and strengthen the cyber defense system. However, challenges are still faced in terms of this crime, even though there is a strong legal foundation, it is necessary to strengthen law enforcement capacity, develop more comprehensive policies in data protection, and increase public awareness